Erratum to: Quantifying the Visual Experience of Three-dimensional Built Environments [Journal of Asian Architecture and Building Engineering, Vol. 17 (2018), No.1, pp.117-124]. Issue 1 (1st January 2018) - Chang, Dongkuk; Park, Joohee
Abstract : Wrong: Acknowledgement This work was supported by the Korea Research Foundation Grant funded by the Korean Government (2015R1D1A1A01059898). Correct: Acknowledgement This study was supported by research fund from Chosun University, 2014.